Two Ways to Kill a Patient. Issue 1 (12th January 2018) - Bronner, Ben
Abstract: According to the Standard View, a doctor who withdraws life-sustaining treatment does not kill the patient but rather allows the patient to die—an important distinction, according to some. I argue that killing (and causing death) can be understood in either of two ways, and given the relevant understanding, the Standard View is insulated from typical criticisms. I conclude by noting several problems for the Standard View that remain to be fully addressed.